Jonh Stuart Mill e o psicologismo: o system of logic nas origens da filosofia contemporanea - Prado, Lucio Lourenço (2006)
This work presents the logic and semantic of John Stuart Mill relating them, on the one hand, to the psychological nominalist tradition represented by John Locke´s theory of ideas, and, on the other hand, to the forthcoming logic semantic discussions of XIX century, mainly from Frege´s philosophy. According to our hypothesis, in opposition to an established interpretative tradition, Mill was responsible for significant theses, among others, in favor of the logicist efforts and anti-psychologists who marked most of the later discussions on the nature of logic. On the one hand, Mill´s criticism to the thesis according to which the significance of language terms are ideas (what he calls conceptualism), in addition to his clear view in distinguishing mental processes in the reasoning act of objective reasons involved in the inferences correction, constituted, according to our conclusions, important positive influence sources, not just to Frege´s philosophy, but to a whole philosophycal tradition that came to contemporary analytical philosophy. The work is divided in three chapters. In the first chapter, important elements of Mill´s logic and semantics are presented, such as: the definition of logic as a proof science, the relationship between logic and language, theory of connotation and some propositions. The second chapter deals with Mill´s criticism of the psychological semantic model represented by, among others, Locke. The third chapter aims to the question whether, from the point of view of Fregean logicism, Mill can be considered a psychologist